Pemantauan Hemodinamik selama Tindakan Transcatheter Closure pada Pasien Patent Ductus Arteriosus - Kusumawati, Eviana Nurul; Oemar, Hamed; Stujanna, Endin Nokik (UHAMKA Press, 2025)
Background: Patent Ductus Arteriosus (PDA) occurs when the blood vessels connecting the aorta and pulmonary artery do not close after birth. Transcatheter closure using a PDA occluder is a first-line treatment, but hemodynamic monitoring is essential as patients may experience sudden declines during the procedure. Methods: A case study involving a 2-year-old female patient with patent ductus arteriosus who underwent transcatheter closure at the Dr Cipto Mangunkusumo National Central Public Hospital (RSCM). Results: Hemodynamic changes were found in patients who were planned for transcatheter closure. Pre-operatively the patient's hemodynamics were stable, but during the action the hemodynamic monitoring decreased and the patient's ECG experienced a change in bradycardia rhythm. Because there is no flow in the pulmonary arteries and reduced blood supply to the lungs when a PDA Occluder will be developed. The technician immediately informed the doctor and team that there was a decrease in hemodynamics and EKG. Doctor gives epinephrine 0.02 mcg IV to patient. Hemodynamics stabilized, the procedure was continued and the PDA occluder was successfully installed. Conclusion: Despite stable pre-operative hemodynamics, hemodynamic monitoring during transcatheter closure in patients with patent ductus arteriosus is essential and should not be neglected.